Common Academic Experiences No One Talks About: Repeated Rejection, Impostor Syndrome, and Burnout. (May 2020) - Jaremka, Lisa M.; Ackerman, Joshua M.; Gawronski, Bertram; Rule, Nicholas O.; Sweeny, Kate; Tropp, Linda R.; Metz, Molly A.; Molina, Ludwin; Ryan, William S.; Vick, S. Brooke
Academic life is full of learning, excitement, and discovery. However, academics also experience professional challenges at various points in their career, including repeated rejection, impostor syndrome, and burnout. These negative experiences are rarely talked about publicly, creating a sense of loneliness and isolation for people who presume they are the only ones affected by such setbacks. However, nearly everyone has these experiences at one time or another; therefore, talking about them should be a normal part of academic life. The goal of this article is to explore and destigmatize the common experiences of rejection, impostor syndrome, and burnout by sharing a collection of short personal stories from scholars at various stages of their careers with various types of academic positions. Josh Ackerman, Kate Sweeny, and Ludwin Molina discuss how they have dealt with repeated rejection. Linda Tropp, Nick Rule, and Brooke Vick share experiences with impostor syndrome. Finally, Bertram Gawronski, Lisa Jaremka, Molly Metz, and Will Ryan discuss how they have experienced burnout.